Corporate governance and earnings management in the Chinese listed companies: A tunneling perspective - Liu, Qiao; Lu, Zhou (Joe) (Journal of Corporate Finance, 2007)
This paper examines the relation between earnings management and corporate governance in China by introducing a tunneling perspective. We document systematic differences in earnings management across the universe of China's listed companies during 1999–2005, and empirically demonstrate that firms with higher corporate governance levels have lower levels of earnings management. We study two China-specific situations, in which the listed firms have strong incentives to manage earnings in order to meet certain return on equity (ROE) thresholds, and earnings management has been shown to be the most conspicuous. We identify tunneling evidence for each. Our empirical findings, although not being able to completely exclude other explanations, strongly suggest that agency conflicts between controlling shareholders and minority investors account for a significant portion of earnings management in China's listed firms.